The zircon archive of continent formation through time - Roberts, N.; Spencer, Christopher (Geological Society Publishing House, 2014)
The strong resilience of the mineral zircon and its ability to host a wealth of isotopic information make it the best deep-time archive of Earth’s continental crust. Zircon is found in most felsic igneous rocks, can be precisely dated and can fingerprint magmatic sources; thus, it has been widely used to document the formation and evolution of continental crust, from pluton- to global-scale. Here, we present a review of major contributions that zircon studies have made in terms of understanding key questions involving the formation of the continents. These include the conditions of continent formation on early Earth, the onset of plate tectonics and subduction, the rate of crustal growth through time and the governing balance of continental addition v. continental loss, and the role of preservation bias in the zircon record.